2010
DOI: 10.1007/s12028-010-9456-9
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Nicotine Replacement Therapy in Cigarette Smokers with Acute Subarachnoid Hemorrhage

Abstract: Despite vasoactive properties, administration of NRT among active smokers with acute SAH appeared to be safe, with similar rates of vasospasm and DCI, and a slightly higher rate of seizures. The association of NRT with lower mortality could be due to chance, to uncontrolled factors, or to a neuroprotective effect of nicotine in active smokers hospitalized with SAH, and should be tested prospectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 48 publications
1
56
0
Order By: Relevance
“…25 Our results also demonstrate possible therapeutic effects of NRT in attenuating clinical vasospasm and improving outcome. Research continues to improve our understanding of the pathogenic mechanisms underlying clinical VSP and in parallel has improved our knowledge of nicotine's physiological and cellular effects making it plausible as a therapeutic target for future study.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…25 Our results also demonstrate possible therapeutic effects of NRT in attenuating clinical vasospasm and improving outcome. Research continues to improve our understanding of the pathogenic mechanisms underlying clinical VSP and in parallel has improved our knowledge of nicotine's physiological and cellular effects making it plausible as a therapeutic target for future study.…”
Section: Discussionsupporting
confidence: 56%
“…22 Current clinical practice deems NRT safe even in patients with cardiac disease except those with active unstable angina or recent myocardial infarction. 23 The literature is extremely limited but most recent studies in the intensive care unit population report no increase in mortality in the medical intensive care unit and neuroscience intensive care units, 24,25 although patients undergoing cardiac surgery did have NRT-associated increases in postoperative mortality and some authors warn that NRT is not harmless and that the further prospective study is necessary. 26 A recent study 25 in patients with SAH even found a mortality benefit at 3 months with NRT.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Transdermal nicotine replacement therapy was provided to smokers of more than 0.5 packs per day. 24,25 Transcranial Doppler imaging was performed daily or every other day at the managing physician's discretion, and a neurological examination was performed every 1 to 2 hours by nurses or physicians. All patients were initially treated in a dedicated neuroscience intensive care unit; a few patients with Hunt and Hess grade I to II SAH deemed at low risk for vasospasm were subsequently managed in a neurological intermediate care unit.…”
Section: Sah Protocolmentioning
confidence: 99%
“…In this case, we tried to decrease the level of sedation and stopped it as soon as possible despite severe agitation, which was probably in part due to nicotine withdrawal. Although the safety of nicotine replacement therapy has been challenged in ICU patients, it appeared to be safe in the SAH population and did not increase the frequency of delayed cerebral ischemia [3]. In a sedated patient, the diagnosis of limb weakness would have probably been delayed.…”
Section: Discussionmentioning
confidence: 99%